"You've Come a Long Way, Baby": The Convergence in Age Patterns of Lung Cancer Mortality by Sex, United States, 1959–2013. (2nd January 2017) - Rivadeneira, Natalie A.; Noymer, Andrew
ABSTRACT: We analyze lung cancer mortality by age and sex in the United States, 1959–2013. It is already known that male lung cancer death rates exceed those of women and that tobacco use is the leading reason for the sex difference. We elaborate on this knowledge by showing that unlike most causes of death, lung cancer mortality patterns by age are a very good fit to a quadratic-Gompertz model, i.e., log mortality rates are quadratic by age, with the mode above age 70. With a little additional historical data on sex differences in tobacco use, the quadratic models help to paint a clear quantitative picture of behavior-led convergence in lung cancer mortality by sex. The shape of the sex-specific mortality curves have converged dramatically: since 1983, the sexes have had statistically indistinguishable shapes of their quadratic-Gompertz mortality curves. Female lung cancer mortality patterns have shown a transformation from a nonsmoking to a smoking pattern. The modal age of the quadratic-Gompertzian lung cancer death rates has potential application in countries at earlier stages of the global tobacco epidemic. Where the modal age is falling (year-on-year), we can infer that the local lung cancer epidemic is getting worse, and where it is rising, that it has begun to abate.